2015
DOI: 10.1088/0960-1317/25/5/055014
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and mechanical characterization of long and different penetrating length neural microelectrode arrays

Abstract: This paper presents a detailed description of the design, fabrication and mechanical characterization of 3D microelectrode arrays (MEA) that comprise high aspect-ratio shafts and different penetrating lengths of electrodes (from 3 mm to 4 mm). The array's design relies only on a bulk silicon substrate dicing saw technology. The encapsulation process is accomplished by a medical epoxy resin and platinum is used as the transduction layer between the probe and neural tissue. The probe's mechanical behaviour can s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…This number matches very well with the 11 mN penetration force through rat dura mater of sharpened silicon probes reported by Fekete et al [46]. Goncalves et al reported that the maximum insertion force of 180 µm wide silicon shank in 0.5% agarose gel is 2.65 mN and 12.5 mN in the porcine brain [47]. After passing this barrier, the insertion force dropped abruptly to 1.4 mN and then slowly increased to 2.0 mN when it stopped at a penetration depth of 11 mm.…”
Section: Insertion Force Characterization Resultssupporting
confidence: 88%
“…This number matches very well with the 11 mN penetration force through rat dura mater of sharpened silicon probes reported by Fekete et al [46]. Goncalves et al reported that the maximum insertion force of 180 µm wide silicon shank in 0.5% agarose gel is 2.65 mN and 12.5 mN in the porcine brain [47]. After passing this barrier, the insertion force dropped abruptly to 1.4 mN and then slowly increased to 2.0 mN when it stopped at a penetration depth of 11 mm.…”
Section: Insertion Force Characterization Resultssupporting
confidence: 88%
“…Nowadays glass insulation is used instead (Bhandari et al, 2009a ). Alternatively, electrodes can be electrically isolated and encapsulated within medical-grade epoxy resin removed from kerfs by dicing (Goncalves et al, 2015 ). In general, standard inorganic passivation layers are not sufficient to provide appropriate level of protection from body environment, thus supplementary encapsulation with polymers such as Parylene-C or polyimide is applied (Loeb et al, 1977 ; Hassler et al, 2011 ).…”
Section: Micromachined Microelectrodesmentioning
confidence: 99%
“…The use of a scanning electron microscope is necessary to monitor the displacement in real-time during the mechanical test. Nanoindenters, tensile machines, or atomic force microscopes inside a scanning electron microscopy (SEM) chamber have been used to test tensile, compression, and bending of micropillars. Although these approaches lead to reliable results, they require expensive and difficult-to-use instrumentation. For these reasons, some early experimental techniques with AFM that do not involve SEM have been proposed.…”
Section: Introductionmentioning
confidence: 99%